Remission of an Intracardiac Melanoma Metastasis after Tremelimumab Therapy - Sebastian Spethmann; Uwe Trefzer; Fabian Knebel (Karger Publishers, 2014)
Tremelimumab is a fully human monoclonal antibody specific for human cytotoxic T lymphocyte-associated antigen 4. Administration of tremelimumab to patients with locally advanced and metastatic melanoma has resulted in a subset of patients with durable objective tumour regressions. Our echocardiographic images impressively show the effects of this new antibody in a patient with cardiac metastatic malignant melanoma.